2011
DOI: 10.1158/0008-5472.sabcs11-s4-8
|View full text |Cite
|
Sign up to set email alerts
|

S4-8: First results of AVEREL, a randomized phase III trial to evaluate bevacizumab (BEV) in combination with trastuzumab (H) + docetaxel (DOC) as first-line therapy for HER2−positive locally recurrent/metastatic breast cancer (LR/mBC)

Abstract: Background: H + taxane is an established and effective first-line treatment for HER2−positive LR/mBC. Preclinical data provide the rationale for combining BEV and H in HER2−positive LR/mBC but clinical data in this setting are limited to single-arm phase II studies. AVEREL is the first randomized trial of BEV in HER2−positive LR/mBC. Methods: Eligible patients had measurable or evaluable HER2−positive LR/mBC (centrally confirmed IHC 3+ or FISH/CISH +), ECOG performance status 0/1, and had receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 0 publications
1
17
0
Order By: Relevance
“…More importantly findings in the clinic show that bevacizumab treatment does not contribute favorably to the effect of trastuzumab and support the idea that vessel normalization by bevacizumab has the same effects in patients. In patients with HER2-positive metastatic breast cancer, the combination of bevacizumab and trastuzumab showed only a minimal-to-no improvement in progression-free survival 20,21). Combination studies of bevacizumab plus another antibody have shown a detrimental or only modestly beneficial effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More importantly findings in the clinic show that bevacizumab treatment does not contribute favorably to the effect of trastuzumab and support the idea that vessel normalization by bevacizumab has the same effects in patients. In patients with HER2-positive metastatic breast cancer, the combination of bevacizumab and trastuzumab showed only a minimal-to-no improvement in progression-free survival 20,21). Combination studies of bevacizumab plus another antibody have shown a detrimental or only modestly beneficial effect.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is no clear evidence yet for this phenomenon at the tumor level, 2 large clinical colon cancer trials have shown that combining bevacizumab with cetuximab or panitumumab was less effective than either antibody alone (18,19). Also, 2 randomized studies in patients with human EGF receptor 2 (HER2)-positive metastatic breast cancer showed disappointing impact of adding bevacizumab to trastuzumab (20,21). It is therefore of interest to clarify whether bevacizumab impairs tumor uptake of other antibodies.…”
Section: Introductionmentioning
confidence: 99%
“…Adding to the controversy, further results of the AVEREL study were recently reported and showed that adding bevacizumab to standard therapy prolongs PFS by about three months in women with HER2-positive locally recurrent or metastatic breast cancer. 25 This benefit of added bevacizumab was similar across most subgroups, except among patients aged 65 years or older and those with measurable disease, in which the benefit was greater. The ORR was significantly higher in the bevacizumab group.…”
Section: Is Overall Survival the Most Important Endpoint In Metastatimentioning
confidence: 85%
“…2 We are hopeful that these controversies will indeed kindle a fire in the research community so that clinical trials are conducted in a smarter and more efficient manner. We also sincerely hope that effective predictive markers, perhaps as suggested by data from A Randomized Phase III Trial to Evaluate Bevacizumab in Combination with Trastuzumab Plus Docetaxel as First-Line Therapy for HERZPositive Locally Recurrent/Metastatic Breast Cancer (AVEREL, NCT00391092), 3 will advance the use of antiangiogenic agents.…”
Section: University Of Pittsburgh Cancer Institute Pittsburgh Pamentioning
confidence: 99%
“…However, it is questionable whether these cutoff values were appropriate, given the known iodine deficiency among young women in the United Kingdom 2 and indeed in a subgroup of women in the trial. 3 If reference ranges derived from iodine-sufficient populations 4,5 had been used, the cutoffs would have been lower for thyrotropin and higher for free thyroxine, thereby increasing the number of women who would have been treated (along with their respective controls). (Incidentally, the units of free thyroxine have been inaccurately converted on page 494 of the article.)…”
Section: Antenatal Thyroid Screening and Childhood Cognitive Functionmentioning
confidence: 99%